2018
DOI: 10.21037/qims.2018.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in neonatal lung disease

Abstract: Lung diseases in neonates can be life-threatening condition and may result in respiratory failure and death. Chest X-ray is a traditional diagnostic technique that results in radiation exposure to patients. Lung ultrasound is a user-friendly imaging technique that has been increasingly used in clinical practice in recent years and presents the advantages of real-time imaging and without radiation. Here we review the sonographic appearances of common neonatal lung diseases and present demonstration of typical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 54 publications
0
30
0
2
Order By: Relevance
“…Also, it is non-invasive, low cost, fast, repeatable and does not require patient transportation outside the ICU [8]. It is as reliable as CT as came in the study done by Algieri et al [9] comparing transthoracic LUS and CT in the assessment of lung aeration, and found a good correlation between them.…”
Section: Discussionmentioning
confidence: 88%
“…Also, it is non-invasive, low cost, fast, repeatable and does not require patient transportation outside the ICU [8]. It is as reliable as CT as came in the study done by Algieri et al [9] comparing transthoracic LUS and CT in the assessment of lung aeration, and found a good correlation between them.…”
Section: Discussionmentioning
confidence: 88%
“…Lung ultrasound is another noninvasive technique used in intensive care units to detect e.g. atelectasis 5 ; however, it is highly user-dependent, gives no information on oxygen distribution, and does not allow for continuous surveillance. In comparison to the above mentioned, the GASMAS technique enables continuous monitoring of the oxygen concentration in the lung as well as an indication of changes in gas volume with one light probe (preferably internal) and one or several detection probes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Research efforts have been directed towards the development of noninvasive alternatives to X-ray imaging. Currently, lung ultrasound imaging 5 can be used for the detection of pneumothorax, consolidated lung parts and pleural effusions (e.g. blood).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, children should avoid CT examination as much as possible. Children are much more sensitive than adults to the induction of cancer by radiation (10,16), and ultrasound imaging can be an alternative to techniques associated with radiation (17,18). CXR can be the choice for imaging, particularly for serial monitoring, as demonstrated in the case report from USA (12).…”
mentioning
confidence: 99%